Economic and environmental consequences of nitrogen application rates, timing and methods on corn in Ontario. (March 2021) - De Laporte, Aaron; Banger, Kamaljit; Weersink, Alfons; Wagner-Riddle, Claudia; Grant, Brian; Smith, Ward
Abstract: Large scale adoption of nitrogen (N) management practices, including the 4Rs, could lead to beneficial environmental and economic outcomes, but only if they improve agricultural profit or are driven by policy and legislation. This study uses a spatial economic maximization and environmental simulation model to examine the economic and environmental tradeoffs of adopting three different 4R practices, specifically N rate reduction, timing (sidedress versus at-planting) and placement methods (broadcast versus injection) in Ontario corn production, under alternative annual weather conditions. The study shows that the use of optimized agronomic, based on meeting crop N requirements specific to each fertilizer management practice, rather than historic, N application increases annual average Ontario-wide farm profit from 124 million to 173 million (39.5%), decreases N application from 122 to 97 kt (20.5%), decreases nitrous oxide (N2 O) emissions from 3.4 to 2.4 kt (29.4%), decreases ammonia (NH3 ) volatilization from 12.4 to 1.2 kt (90.3%) and decreases nitrate (NO3 − ) leaching from 47 to 13 kt (72.3%), over 30-years of weather data. Injection and sidedress appear to be more N use efficient than broadcast, with sidedress becoming increasingly important as N prices and constraints increase. N2 O emissions appear to be more difficult to mitigate compared to NH3 emissions and NO3 − leaching. Regarding the 4Rs, right placement and right timing play a role under specific spatial conditions, while right rate appears to be the most effective means to mitigate the environmental impacts of corn N application and may be mutually beneficial to farmers and society. Highlights: Optimized agronomic N rates increase profit and decrease environmental N losses. Injection and sidedress become more important as N prices and constraints increase. N2 O emissions are more difficult to mitigate than NH3 emissions and NO3 − leaching. 4R right placement and right timing have a role but right rate is more effective.